PERTUMBUHAN EKONOMI, MORALITAS DAN KESADARAN PEMERINTAH DAERAH TERHADAP KELEMAHAN PENGENDALIAN INTERNAL SETELAH MASA PANDEMI COVID-19 SEMALANG RAYA - Risnaningsih, Risnaningsih; Ekasari, Luh Dina; Widhi Yanti, Dyah Agustin; A. Ambu, Debi Jiara (Unitri Press, 2024)
The goal of this analysis is to determine how changes in monetary growth, moral standards, and local government awareness affect weaknesses in internal regulation during the coronavirus. This investigation uses quantitative information. Financial progress, moral character, and acquaintance with local governance are the subjects of this assessment. Meetings, documentation, perception, and using polls were used to aid in the information collection process. Utilising several straight relapse tests, information research was accomplished. The study's findings indicate that the lack of interior control during the coronavirus pandemic is not primarily influenced by financial development, profound quality, or territorial government awareness